Differences in insulin treatment satisfaction following randomized addition of biphasic, prandial or basal insulin to oral therapy in type 2 diabetes. - Farmer, A; Oke, J; Stevens, R; Holman, R (2011)
AIM: No differences in patient health status as measured by the EuroQol-5 Dimension (EQ-5D) questionnaire were observed at 1 year between groups randomized to addition of biphasic, prandial or basal insulin to oral therapy in the treat-to-target in type 2 diabetes trial. We further investigated insulin treatment satisfaction between groups. METHODS: Seven hundred and eight patients with suboptimal glycated haemoglobin levels (7.0-10.0%) taking maximally tolerated doses of metformin and sulphonylurea were randomized to biphasic insulin aspart twice-daily, prandial insulin aspart three times daily or basal insulin detemir once-daily (twice if required). At 1 year self-completed Insulin Treatment Satisfaction Questionnaires (ITSQ) were administered. Lower scores indicated lower treatment satisfaction. We tested for differences between the three groups for the ITSQ total score and for each of the five ITSQ domain scores adjusting for age, gender, ethnicity and education. RESULTS: All 22 ITSQ subscales were completed by 554 (78.2%) patients. Their mean (s.d.) age was 61.5 (9.4) years, body weight 86.1 (16) kg and median (IQR) diabetes duration 9 (6-13) years. Sixty-five percent (358) were male. Median (IQR) 1-year ITSQ total score was lower in patients allocated to prandial therapy (76.5, 68.0-88.6) than in patients allocated to biphasic insulin (83.3, 74.2-90.2) or basal insulin (84.1, 73.5-93.2). With the exception of 'perceived glycaemic control', 1-year adjusted ITSQ scores were significantly different between groups for each of the ITSQ domains, with lower scores for prandial insulin compared with the basal or biphasic groups. Median (IQR) ITSQ scores were lower in patients with a gain in body mass index (BMI) > 1.23 kg/m² over 1 year (79.5, 69.7-89.4) compared to those with a lesser or no gain in BMI (84.1, 74.2-92.4) and in those with occurrence of hypoglycaemia (79.5, 69.7-88.6) compared to those with no hypoglycaemia (84.1, 73.7-93.2). CONCLUSION: Specific measurement of insulin treatment satisfaction identifies differences between regimens used to intensify treatment for type 2 diabetes. Impact of treatment on lifestyle needs to be considered as a factor in the choice of an insulin regimen.